2019
DOI: 10.1590/1981-6723.16918
|View full text |Cite
|
Sign up to set email alerts
|

Effect of freezing with oscillating magnetic fields on the physical and sensorial characteristics of mango (Mangifera indica L. cv. ‘Kent’)

Abstract: Freezing using oscillating magnetic fields (OMF), was developed and is marketed to overcome drawbacks that normally occur in conventional freezing, which affect firmness, colour, taste, and drip loss in frozen-thawed foods. In order to verify the aforementioned advantages, the effect of freezing using OMF on cubes of mango (Mangifera indica L. cv. ‘Kent’) was evaluated. The cubes were frozen at -30 °C for 35 min with OMF set at 0, 30%, 50%, 75% and 100%, and then immediately thawed at room temperature (25 °C) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 18 publications
2
8
0
1
Order By: Relevance
“…Puza et al. (2019) investigated the effects of cell alive system on mango physiology and sensory evaluations by freezing the sample with an oscillating magnetic field under the strength of 0, 50, 75, and100 at −30°C for 35 min and then immediately thawed to evaluate texture test sensory evaluation. The results show that the product quality is retained to a certain extent.…”
Section: Novel Synergistic Freezing Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…Puza et al. (2019) investigated the effects of cell alive system on mango physiology and sensory evaluations by freezing the sample with an oscillating magnetic field under the strength of 0, 50, 75, and100 at −30°C for 35 min and then immediately thawed to evaluate texture test sensory evaluation. The results show that the product quality is retained to a certain extent.…”
Section: Novel Synergistic Freezing Technologymentioning
confidence: 99%
“…It is said that the cell alive system causes considerable overcooling of the product, after which uniform nucleation and instant freezing of the entire product will occur (Puza et al., 2019). Studies have shown that the oscillating effect of the magnetic field can prevent the excessive accumulation of water molecules during the freezing, thereby preventing the formation of larger ice crystals (Shikata et al., 2016).…”
Section: Novel Synergistic Freezing Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…This equipment had a control panel, where process parameters are programmed: i) cooling temperature; ii) ventilation speed during cooling (50% cooling FAN equivalent to 1.9 m/s (Otero et al, 2017)); iii) CAS freezing temperature; iv) ventilation rate (programmed to 50% CAS FAN equivalent to 1.9 m/s (Otero et al, 2017)) during CAS freezing; v) CAS energy; and vi) freezing time. Puza et al (2019) could describe the most important description of dimensions, number of trays, among others. Likewise, measurements of OMF were reported by Otero et al (2017), who indicated variations in OMF (less than 1 mT) inside the CAS freezer and a maximum of 60 Hz for 100% CAS energy.…”
Section: Processing and Freezing Assisted With Electromagnetic Fieldsmentioning
confidence: 99%
“…Experimental studies have been carried out using the CAS freezer. The quality of thawed foods such as mackerel muscle (Okuda et al, 2020), cherry (Tang et al, 2020), mango cubes (Puza et al, 2019), crab sticks (Otero et al, 2017), garlic bulbs (James et al, 2015), chicken breasts (Yamamoto et al, 2005) were evaluated and compared to traditional freezing, however not all studies did not report considerable advantages for CAS freezing. For CAS freezing, some advantages were reported concerning parameters (time) of the freezing process, but the decrease in firmness also occurs in traditional freezing.…”
Section: Introductionmentioning
confidence: 99%